Evaluation of postoperative wound infection in children - Majumder, Partha Sarathy; Karmaker, Anuradha; Alam, Md Mahbubul; Nessa, Lutfan (Journal of Paediatric Surgeons of Bangladesh, 2018)
This study was conducted to assess postoperative wound infection in children. It was also decided to estimate the rate of wound infection in children and to identify the factor that best predicts postoperative wound infection in children. This prospective study was carried out in the Department of Paediatric Surgery, BSMMU, Dhaka during the period of January 2009 to September 2010 and included consecutive 100 children undergoing routine surgery. The children were assessed during the first 30 postoperative days for the evidence of wound infection that were confirmed by culture and sensitivity. This study shows majority of the children were found in the age group of 13 – 60 months in both groups. The mean (±SD) age was 67.74±58.25 months with ranged from 13 months to 180 months. It was found that majority were male (73%). The post operative wound infection was 16% and the status of wound infection according to nature of wound was assessed and found that 7(43.8%) were clean and 9(56.2%) were potentially contaminated among the children who had wound infection. However, 65(77.4%) and 19(22.6%) were clean and potentially contaminated respectively among the children who didn’t had any wound infection. The status of would infection according to BMI was assessed and found that BMI ˂20 kg/m2 in 15(93.8%) children who had wound infection and in 61(72.6%) of the children who didn’t had any wound infection. BMI 20 – 25 kg/m2 was in 1(6.2%) child who had wound infection and in 23(27.4%) of children who had no wound infection. The status of would infection according to serum albumin was assessed and found that serum albumin ˂35 gm/L was in 14(87.5%) of the children who had wound infection and 4(4.8%) of the children who didn’t had any wound infection. Serum albumin level ³35 gm/L in 2(12.5%) of children who had wound infection and in 80(95.2%) of the children who had no wound infection. An increased rate of wound infection was associated with operative procedures longer than 1 hour and with the presence of an associated illness. It could be concluded that the greatest risk factors were those associated with local contamination of the surgical wound. Journal of Paediatric Surgeons of Bangladesh (2017) Vol. 8 (1): 11-14